Metabolomics and quantitative analysis to determine differences in the geographical origins and species of Chinese dragon’s blood - Sun, Xiuting; Huang, Qing; Wu, Mingsong; He, Liu; Zhao, Xiangsheng; Yang, Xinquan (Frontiers in Plant Science, 2024)
The aim of this study was to comprehensively analyze the differences in Chinese dragon's blood (CDB), specifically Dracaena cochinchinensis and Dracaena cambodiana, from different geographical origins. Methods: Metabolomic analysis of CDB was performed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). A reliable ultra-performance liquid chromatography method with a photodiode array detector (UHPLC-PDA) was developed and applied for the quantitative analysis of 12 phenolic compounds in 51 batches of samples. Results: A total of 1394 metabolites were detected and annotated, of which 467 were identified as differentially accumulated metabolites. Multivariate analysis revealed that both origin and species had an effect on the composition of CDB, with greater variation between species. 19 phenolic compounds were selected as quality markers to distinguish D. cochinchinensis (Hdsp) from D. cambodiana (Hdca), and oppositin and spinoflavanone a were identified as quality markers to discriminate D. cochinchinensis samples from Hainan (Hdsp) and Guangxi Provinces (Gdc).Quantitative analysis indicated that four phenolic compounds, including loureirin D, 4H-1-benzopyran-4-one,2,3-dihydro-3,5,7-trihydroxy-3-[(4-methoxyphenyl)methyl]-,(R)-, loureirin B, and pterostilbene, showed significant differences between Gdc and Hdsp. Additionally, five phenolic compounds, namely resveratrol, loureirin D, pinostilbene, 4H-1-benzopyran-4-one,2,3-dihydro-3,5,7-trihydroxy-3-[(4methoxyphenyl)methyl]-, (R)-, and loureirin B, exhibited significant differences between Hdsp and Hdca. Conclusion: There are significant differences in the quality of CDB from different geographical origins and species, which lays the foundation for the in-depth development and utilization of different sources of CDB.